1987
DOI: 10.1111/j.1432-1033.1987.tb11207.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited proteolysis reveals low‐affinity binding of N‐acetyl‐L‐glutamate to rat‐liver carbamoyl‐phosphate synthetase (ammonia)

Abstract: Carbamoyl-phosphate synthetase was inactivated by elastase with first-order kinetics, and N-acetyl-Lglutamate speeded inactivation. From the dependence of the tlI2 value for inactivation on the concentration of acetylglutamate we estimate a Kd value for binding of the activator of 0.365 mM, which is approximately 600 times greater than in the presence of ATP, HCO;, K + and MgZf. K + and Mg2+ are not required for binding with low affinity, and in the absence of ATP they do not appear to increase the affinity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Limited proteolysis has been used to delineate the structural organization of several amidotransferases including asparagine synthase [43], carbamoyl phosphate synthase [44–50], anthranilate synthase [51], and glucosamine‐6‐phosphate synthase [52]. This methodology has been particularly useful for identifying both ligand‐binding sites and, in the case with glucosamine‐6‐phosphate synthase, an exposed ‘hinge’ region that, when cleaved by α‐chymotrypsin, led to separation of the enzyme into its GAT and synthase domains.…”
Section: Discussionmentioning
confidence: 99%
“…Limited proteolysis has been used to delineate the structural organization of several amidotransferases including asparagine synthase [43], carbamoyl phosphate synthase [44–50], anthranilate synthase [51], and glucosamine‐6‐phosphate synthase [52]. This methodology has been particularly useful for identifying both ligand‐binding sites and, in the case with glucosamine‐6‐phosphate synthase, an exposed ‘hinge’ region that, when cleaved by α‐chymotrypsin, led to separation of the enzyme into its GAT and synthase domains.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this site may adopt high-and low-affinity conformations [2,6,71. The former is adopted in the central complex [2], and thus predominates under the conditions of ~131.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE analysis indicated Ն 95% purity for all constructions. Because protease treatments necessary to remove fusion partners also result in proteolysis of fCPS, presumably at the links between domains (13)(14)(15)(16), in the present studies we retained the tag in all fCPS constructions.…”
Section: Methodsmentioning
confidence: 99%